2015
DOI: 10.1016/j.jvs.2015.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Suprarenal versus infrarenal stent graft fixation on renal complications after endovascular aneurysm repair

Abstract: There is no difference in the risk of postoperative renal complications when comparing stent grafts using SR vs IR fixation, particularly with newer-generation devices. Contemporary comparative studies with longer-term follow-up are warranted to further elucidate the influence of SR and IR fixation on renal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…These include rates reported by Pisimisis (Infrarenal: 15% vs. Suprarenal: 19%), Alsac (Infrarenal: 30% vs. Suprarenal: 26%), and Miller (Infrarenal: 12.1% vs. Suprarenal: 12.3%). 710, 19, 20 Notably, however, several of these studies report outcomes from different time points, including mid-term as well as 30-day outcomes. Additionally, overall improvements in patient outcomes following EVAR have likely occurred over the last decade, related to surgeon experience and device evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include rates reported by Pisimisis (Infrarenal: 15% vs. Suprarenal: 19%), Alsac (Infrarenal: 30% vs. Suprarenal: 26%), and Miller (Infrarenal: 12.1% vs. Suprarenal: 12.3%). 710, 19, 20 Notably, however, several of these studies report outcomes from different time points, including mid-term as well as 30-day outcomes. Additionally, overall improvements in patient outcomes following EVAR have likely occurred over the last decade, related to surgeon experience and device evolution.…”
Section: Discussionmentioning
confidence: 99%
“…10, 22 Walsh et al included 11 studies between 1998 and 2006 and found increased renal impairment following suprarenal fixation. However, this effect was eliminated after adjustment for the significant heterogeneity of studies, and the authors concluded that given limitations of current reports, the data were insufficient to determine the precise effect of suprarenal fixation on renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is concern that the suprarenal stent proximal fixation across the renal artery ostia could result in renal dysfunction. However, there are controversial reports in literature and in a recent systematic review regarding suprarenal versus infrarenal stent graft fixation location did not show a significant difference in postoperative renal complications (23). Similarly, endograft coverage and sacrifice of accessory renal arteries may occur, but this has not been shown to correlate with increased renal dysfunction despite correlation with increased renal infarction volume (20,24,25).…”
Section: Renal Arterymentioning
confidence: 97%
“…In a retrospective case-matched analysis of 726 patients, EVAR (with suprarenal fixation EVAR 9 infrarenal fixation) led to greater decrease in eGFR than open aortic repair [60]. However, a meta-analysis (n = 4,474) showed no difference between suprarenal fixation versus infra-renal fixation devices [61]. In a retrospective study of 1,756 patients, EVAR was shown to have a less deleterious effect on renal function than open surgery in patients with pre-operative renal dysfunction [62].…”
Section: Renal Functionmentioning
confidence: 99%